Different sources of forage with crude glycerin in diets with higher percentage of concentrate to beef cattle - Ribeiro, Andressa Ferreira [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This trial aimed to evaluate the effects of feeding different sources of forage in diets with crude glycerin included in 10% of DM diet, on intake, digestibility, ruminal fermentation and microbiology, performance, methane emission, carcass and meat quality traits of Nellore cattle finished in feedlot. The treatments consisting in different sources of forage: Corn silage (CS), Sugar cane (SC) and Sugar cane bagasse (SB), in diets with crude glycerin (10% DM) with higher concentrate proportion. For such study two experiments were conducted: Experiment 1: Nine ruminally cannulated Nellore steers (300.0 ± 30kg and 20 ± 2 months of age) were used in a 3 × 3 Latin Square experimental design with three treatments and three animals in three simultaneous triplicates. There was no effect of different sources of forage with crude glycerin on dry matter (DM), organic matter (OM) and crude protein (CP) intake. The intake of neutral detergent fiber (NDF) increased (P<0.05) in animals fed CS that did not differ from animal fed with SB. Furthermore, animals fed with SB decreased non-fibrous carbohydrate (NFC) intake (P<0.05). Animals fed with CS increased digestibility of DM and NDF compared with the other diets (P<0.05). The NFC digestibility increased in animals fed with SC (P<0.05). Animals fed with SB increased pH values which not differed from animals fed with SC (P<0.05). Animals fed with SC decreased NH3-N values (P<0.05). The protozoa population was not influenced by the different sources of forage in diets with crude glycerin, except Dasytricha and Isotricha. The population of fibrolytic bacteria (Ruminococus flavefaciens, Ruminococcus albus and Fibrobacter succinogenes) were similar (P>0.05) among diets. On the other hand, the population of Selenomonas ruminantium, was higher (P<0.01) in animals fed with CS. Experiment 2: There were used 40 Nellore young bulls, however, 10 animals (396.6 ± 34.7 kg 24 ± 2 months of age) were slaughtered ...

Este trabalho teve como objetivo avaliar os efeitos da alimentação com diferentes fontes de forragem em dietas com 10% glicerina bruta incluída na MS sobre o consumo, digestibilidade, fermentação ruminal, desempenho, características de carcaça, qualidade da carne e emissão de metano entérico de bovinos Nelore terminados em confinamento. Os tratamentos consistiam em diferentes fontes de forragem (FDN da forragem fixado em 15%): Silagem de milho (SM), Cana de açúcar (CA) e Bagaço de cana (BC) em dietas com glicerina bruta (10% MS). Para tal estudo foram conduzidos dois experimentos: Experimento 1: Nove novilhos Nelore canulados no rúmen (300 ± 30 kg e 18 ± 2 meses de idade) foram utilizados em delineamento de quadrado latino (3x3), três tratamentos e três períodos em três repetições simultâneas para avaliar o consumo, digestibilidade, fermentação e microbiota ruminal. Não houve efeitos das diferentes fontes de forragem em dietas com glicerina bruta no consumo de matéria seca (MS), matéria orgânica (MO) e proteína bruta (PB) (P>0.05). O consumo de fibra em detergente neutro (FDN) foi maior em animais alimentados com SM que não diferiu de animais alimentados com BC (P<0.05). Além disso, animais alimentados com BC apresentaram menor consumo de carboidratos não fibrosos (CNF; P<0.01). Animais alimentados com SM apresentaram maior digestibilidade da matéria seca MS e FDN comparada com as outras dietas. Animais alimentados com CA apresentaram maior digestibilidade de CNF (P<0.05). Adicionalmente, os animais alimentados com BC apresentaram maior digestibilidade da PB e não diferiram dos animais alimentados com silagem de milho. Animais alimentados com BC apresentaram os maiores valores de pH que não diferiu de animais alimentados com CA. Além disso, os animais alimentados com CA apresentaram os menores valores de nitrogênio amoniacal (NH3-N). A população de protozoários foi similar entre os tratamentos exceto ...
Keywords: Bovino de corte - Nutrição; Forragem; Glicerina; Ruminante - Alimentação e rações; Bacterias; Milho - Silagem; Cana-de-açúcar; Forage